1992
DOI: 10.1128/jvi.66.7.3996-4002.1992
|View full text |Cite
|
Sign up to set email alerts
|

Posttranslational side chain modification of a viral epitope results in diminished recognition by specific T cells

Abstract: A stretch of 16 amino acid residues within the nominal phosphoprotein of rabies virus was shown to carry an immunodominant epitope for class I-and class II-restricted T cells. The nominal phosphoprotein of rabies virus is thought to be heterogeneously phosphorylated at multiple serine and threonine residues. The synthetic peptide that expressed the T-cell epitope contained a single serine residue corresponding to position 196 of the protein. Phosphorylation of this serine within the synthetic peptide caused a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…A few amino acid shift in the stretch of the epitopic residues after phosphorylation was found earlier for polyclonal antibodies anti-T3 and anti-T3P (Lang et al, 1992b). Similar shift in the binding to major histocompatibility complex was observed for the major T cell epitopic peptide of the phosphoprotein of rabies virus (Larson et al, 1992). The identification and the determination of the number of the required phosphate groups of the minimal epitope for mAb AT8 is in progress.…”
Section: O W L [ N M Lmentioning
confidence: 54%
“…A few amino acid shift in the stretch of the epitopic residues after phosphorylation was found earlier for polyclonal antibodies anti-T3 and anti-T3P (Lang et al, 1992b). Similar shift in the binding to major histocompatibility complex was observed for the major T cell epitopic peptide of the phosphoprotein of rabies virus (Larson et al, 1992). The identification and the determination of the number of the required phosphate groups of the minimal epitope for mAb AT8 is in progress.…”
Section: O W L [ N M Lmentioning
confidence: 54%
“…These modifications include deamidation of asparagine (10,11), cysteinylation of cysteine (12)(13)(14), and glycosylation (15). Posttranslational modification alters the ability of T lymphocytes to recognize MHC class I-or class IIrestricted epitopes (10,(12)(13)(14)(15)(16)(17). Recently, Hogan et al (18) identified the only published example of a naturally processed and presented phosphorylated peptide associated with any MHC molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Fine structures of the rabies virus P protein, however, have not yet been studied precisely, except for some reports that described possible binding domains involved in N-P complex formation and their possible locations at both the N-and C-terminal portions of P protein (9,15). Phosphorylated amino acids of the P protein were identified as serine and threonine (22), but the phosphorylation sites have not yet been identified. Functions of the rabies virus P protein are also thought to be regulated by phosphorylation and dephosphorylation, which however, has not yet been evidenced.…”
mentioning
confidence: 99%